Adsorption of Methylene Blue Using Composite Fe3O4-Ihau Fruit Peel Powder (Dimocarpus longan var. malesianus Leenh.) - Arisa, Putri; Wirawan, Teguh; Widodo, Nanang Tri (Indonesian Journal of Chemical Research, 2025)
A study has been conducted on the adsorption of methylene blue dye using Fe3O4-ihau fruit peel powder composite as the adsorbent. The Fe3O4-ihau fruit peel powder composite adsorbent was synthesized using the co-precipitation method from FeSO4.7H2O and FeCl3.6H2O in a 3:2 ratio, then composited with ihau fruit peel powder. The resulting Fe3O4-ihau fruit peel powder composite was characterized using Fourier Transform Infra-Red (FTIR), Scanning Electron Microscopy (SEM), and X-Ray Diffractometer (XRD). FTIR characterization results of the Fe3O4-ihau fruit peel powder composite showed an absorption peak at a wave number of 586.36 cm-1, corresponding to the Fe-O group. SEM revealed that the Fe3O4-ihau fruit peel powder composite has an uneven surface and smaller pores compared to the ihau fruit peel powder, and XRD showed a diffractogram of the Fe3O4-ihau fruit peel powder composite that closely resembled that of Fe3O4. Methylene blue adsorption by the Fe3O4-ihau fruit peel powder composite adsorbent was optimal at pH 4 with an optimum contact time of 75 minutes, and it had a maximum adsorption capacity of 43.7267 mg/g. The adsorption isotherm followed the Langmuir isotherm, and the adsorption of methylene blue dye using Fe3O4-ihau fruit peel powder composite adsorbent occurs spontaneously, endothermically, and by physisorption.